The Use of Tiktok As A Medium For Education On Sexual Violence From A Psychological Perspective - Faatiya, Aisyah; Aharen, Reina; Adyastika, Clara Faudia; Syifa, Meida Arofatus; Gestania, Najia Ayu; Quddus, Siti Najmi Qamariatul; Sahila, Wardah; Rachman, Yunita Aulia; Yodsuban, Pairin (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
The prevalence of sexual violence globally averages 35.6%, meaning that one in three Indonesian women has personally experienced sexual violence, at least by a partner, loved one or stranger (annual report). According to Komnas Perempuan, there were 93,960 incidents of sexual violence reported between 2001 and 2011. This means that at least 35 women, including children, were victims of sexual violence. Based on Komnas Perempuan's annual report, the prevalence of sexual violence in 2014 was around 2,274 cases (26%), with violence occurring within the household, i.e. within the household or in personal relationships. Cases (56%) occurred in urban areas. Komnas Perempuan also found that incidents of sexual violence accounted for 400,939 of the total incidents of sexual violence against women reported in the last 13 years. the factor in the occurrence of sexual violence is due to economic factors. because economic factors make low human resources and the level of education is lacking. but nowadays even people with low economies have gadgets and can also access social media applications such as tiktok and others. Therefore we use this media method as a learning material that can be accessed by everyone and can also be a reference for their learning. our goal is to introduce sexual violence in order to reduce acts of violence around us.